2017
DOI: 10.4025/psicolestud.v21i4.31806
|View full text |Cite
|
Sign up to set email alerts
|

Brincar E Realidade: Verbalizações De Crianças Em Situação De Acolhimento Institucional

Abstract: RESUMO.Este estudo objetivou analisar as verbalizações de crianças em situação de acolhimento institucional acerca de suas formas relacionais no ambiente. Foram utilizados uma maquete e bonecos para representar a instituição e as pessoas, respectivamente. Participaram da pesquisa seis crianças entre cinco e sete anos, com tempo de acolhimento institucional variando entre três e dezessete meses. Os dados coletados foram filmados, transcritos e sistematizados com base na análise de conteúdo fundamentado na teori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Regarding the category of photographs of physical space, the courtyard, corridor, living room, cafeteria and bedroom were identified, and the interaction and the playful aspect were highlighted. The experience of playing in the context of the sheltering institution represents for the child a way to enter the concrete reality, which allows to develop the notion of transforming agent of their social context (Pedroso et al, 2016). Thus, we observed that the performance of the participants of this research facilitates the expression of the child's play, which occurs through creativity and interaction in the institutional sheltering environment.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Regarding the category of photographs of physical space, the courtyard, corridor, living room, cafeteria and bedroom were identified, and the interaction and the playful aspect were highlighted. The experience of playing in the context of the sheltering institution represents for the child a way to enter the concrete reality, which allows to develop the notion of transforming agent of their social context (Pedroso et al, 2016). Thus, we observed that the performance of the participants of this research facilitates the expression of the child's play, which occurs through creativity and interaction in the institutional sheltering environment.…”
Section: Discussionmentioning
confidence: 67%
“…The analysis of quality of care highlights the relevance of scientific investigations with social educators, because research was conducted on the following aspects: socio-educational planning (Souza, Moreira, & Pereira, 2017), training (Strong, 2018), and the role of this professional in the residential group home (Costa et al, 2018). Furthermore, the literature has explored the association between social educator and institutionalized child or adolescent (Jiménez, 2017;Pedroso, Lobato, & Magalhães, 2016).…”
mentioning
confidence: 99%
“…The gradual construction of rules, the physical limits of the institution and the affective relationship can serve as a form of container for the impulses of the children and adolescents received. This environmental protection is a form of care developed in an institutional environment that is based on containment, that is, the loan of real, affective and symbolic resources by the care providers that facilitate the development process (Pedroso, Lobato, & Magalhães, 2016).…”
Section: Setting: Attention To Basic Needs and Construction Of A Routinementioning
confidence: 99%
“…Caregivers and other children establish relationships with a degree of affection (GABATZ, 2018). The quality of this care provided will always be linked to a figure who is present and continues its development, creating emotional connections, stability, care and security (PEDROSO, 2016). According to the Universal Declaration of Children's Rights (1990), "Children and adolescents have the right to information, culture, leisure, sports, entertainment, entertainment and products and services that respect their peculiar condition as a developing person. "…”
Section: Introductionmentioning
confidence: 99%